Both the folate cycle and betaine‐homocysteine methyltransferase contribute methyl groups for DNA methylation in mouse blastocysts. Issue 3 (2nd December 2014) - Zhang, Baohua; Denomme, Michelle M.; White, Carlee R.; Leung, Kit‐Yi; Lee, Martin B.; Greene, Nicholas D. E.; Mann, Mellissa R. W.; Trasler, Jacquetta M.; Baltz, Jay M.
Abstract : The embryonic pattern of global DNA methylation is first established in the inner cell mass (ICM) of the mouse blastocyst. The methyl donor S ‐adenosylmethionine (SAM) is produced in most cells through the folate cycle, but only a few cell types generate SAM from betaine ( N, N, N ‐trimethylglycine) via betaine‐homocysteine methyltransferase (BHMT)' which is expressed in the mouse ICM. Here, mean ICM cell numbers decreased from 18‐19 in controls to 11‐13 when the folate cycle was inhibited by the antifolate methotrexate and to 12‐14 when BHMT expression was knocked down by antisense morpholinos. Inhibiting both pathways, however, much more severely affected ICM development (7‐8 cells). Total SAM levels in mouse blastocysts decreased significantly only when both pathways were inhibited (from 3.1 to 1.6 pmol/100 blastocysts). DNA methylation, detected as 5‐methylcytosine (5‐MeC) immunofluorescence in isolated ICMs, was minimally affected by inhibition of either pathway alone but decreased by at least 45‐55% when both BHMT and the folate cycle were inhibited simultaneously. Effects on cell numbers and 5‐MeC levels in the ICM were completely rescued by methionine (immediate SAM precursor) or SAM. Both the folate cycle and betaine/BHMT appear to contribute to a methyl pool required for normal ICM development and establishing initial embryonic DNA methylation.—Zhang, B., Denomme, M.M., White, C. R., Leung, K.‐Y., Lee, M. B., Greene, N. D. E. Mann, M. R. W. Trasler, J. M., Baltz, J. M., Both the folate cycle and betaine‐homocysteine methyltransferase contribute methyl groups for DNA methylation in mouse blastocysts. FASEB J. 29, 1069–1079 (2015). www.fasebj.org